Combined effects of host genetics and diet on porcine intestinal fungi and their pathogenic genes - Wang, Tao; Liu, Jiahao; Luo, Yuheng; Yu, Bing; Kong, Xiangfeng; Zheng, Ping; Huang, Zhiqing; Mao, Xiangbing; Yu, Jie; Luo, Junqiu; Yan, Hui; He, Jun (Frontiers in Microbiology, 2023)
As research on gut microbes progresses, it becomes increasingly clear that a small family of microbiota–fungi, plays a crucial role in animal health. However, little is known about the fungal composition in the pig intestine, especially after a dietary fiber diet and hybrid genetics, and the changes in host pathogenicity-associated genes they carry. The purpose of this study is to investigate the effects of diet and genetics on the diversity and structure of porcine intestinal fungi and to describe, for the first time, the host pathogenicityrelated genes carried by porcine intestinal fungi. Samples of colonic contents were collected for metagenomic analysis using a 3 × 2 parsing design, where three pig breeds (Taoyuan, Duroc, and crossbred Xiangcun) were fed high or low fiber diets (n = 10). In all samples, we identified a total of 281 identifiable fungal genera, with Ascomycota and Microsporidia being the most abundant fungi. Compared to Duroc pigs, Taoyuan and Xiangcun pigs had higher fungal richness. Interestingly, the fiber diet significantly reduced the abundance of the pathogenic fungus Mucor and significantly increased the abundance of the fiber digestion-associated fungus Neocallimastix. Pathogenic fungi exert their pathogenicity through the genes they carry that are associated with host pathogenicity. Therefore, we obtained 839 pathogenicity genes carried by the spectrum of fungi in the pig intestine by comparing the PHI-base database. Our results showed that fungi in the colon of Taoyuan pigs carried the highest abundance of different classes of host pathogenicity-related genes, and the lowest in Duroc pigs. Specifically, Taoyuan pigs carried high abundance of animal pathogenicity-related genes (CaTUP1, CPAR2_106400, CaCDC35, Tfp1, CaMNT2), and CaTUP1 was the key gene for Candida pathogenicity. The intestinal fungal composition of crossbred Xiangcun pigs and the abundance of host pathogenicity-associated genes they carried exhibited a mixture of characteristics of Taoyuan and Duroc pigs. In conclusion, our results provide the first comprehensive report on the effects of dietary fiber and genetics on the composition of intestinal fungi and the host-associated pathogenicity genes they carry in pigs. These findings provide a reference for subsequent pig breeding and development of anti-pathogenic fungal drugs.